Historic K-rich silicate glass surface alteration: Behaviour of high-silica content matrices. (December 2018) - Rodrigues, Alexandra; Fearn, Sarah; Vilarigues, Márcia
Graphical abstract: Highlights: The two K-Ca-Si glass compositions show different alteration behaviour. Glass structure plays a dominant role in early stages under similar ageing conditions. The Pb 2+ and Ca 2+ content may relate with more reactive structural arrangements. Preservation state of extant pieces agrees with the replica's early stages. Abstract: Several K-Ca-Si glass compositions typical of Central-European glassworks are susceptible to damage beyond recall, even in mild museum conservative conditions. In order to provide a comprehensive picture of the deterioration process, replica samples were produced and exposed to four different museum-like environments. The corrosion experiment was followed by the use of ToF-SIMS, μ -Raman and μ -FTIR, performing a systematic compositional and structural study for the early stages (one year) of surface alteration. This work demonstrates the dominant role of Pb 2+ and Ca 2+ content for the inferable existence of connected conduction pathways, with strong implications on the surface's hydration, alkali-diffusion and hydrolysis.